2020
DOI: 10.21203/rs.3.rs-74853/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Adverse Childhood Experiences and Depression Among Women in Rural Pakistan

Abstract: BackgroundAdverse Childhood Experiences (ACEs) are a common pathway to adult depression. This pathway is particularly important during the perinatal period when women are at an elevated risk for depression. However, this relationship has not been explored in South Asia. This study estimates the association between ACEs and women’s (N=889) depression at 36 months postpartum in rural Pakistan.MethodData come from the Bachpan Cohort study. To capture ACEs, an adapted version of the ACE-International Questionnaire… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Although such explorations are beyond the scope of the current paper, important factors, such as maternal depression and parenting practices, may mediate the relationship between maternal ACEs and child outcomes. Previous work from our group demonstrated that ACEs were associated with greater depressive symptoms and major depressive episodes [74]. Studies in Kenya found that maternal mental health mediated the relationship between maternal ACEs and child mental health problems [17,18].…”
Section: (Which Was Not Certified By Peer Review)mentioning
confidence: 84%
“…Although such explorations are beyond the scope of the current paper, important factors, such as maternal depression and parenting practices, may mediate the relationship between maternal ACEs and child outcomes. Previous work from our group demonstrated that ACEs were associated with greater depressive symptoms and major depressive episodes [74]. Studies in Kenya found that maternal mental health mediated the relationship between maternal ACEs and child mental health problems [17,18].…”
Section: (Which Was Not Certified By Peer Review)mentioning
confidence: 84%
“…For instance, Negriff (2020) found that in the United States, experiencing neglect, but not physical abuse, predicted anxiety symptoms in adolescence and ACEs related to child maltreatment were more predictive of mental health outcomes than ACEs related to household dysfunction (12). In our team's prior work with a cohort of women in Pakistan at 36 months postpartum, we have found that exposure to community violence was much more strongly correlated with maternal depression than other domains such as neglect (13). A key potential driver of different ndings is the diversity of social, economic, and cultural contexts in which the ACEs take place.…”
Section: Introductionmentioning
confidence: 80%